Análises fenotípicas e moleculares na identificação de SNPs associados aos conteúdos de proteínas total e de reserva de soja [Glycine max (L.) Merril] - Lorenzoni, Rodrigo Monte (2020)
Soybean (Glycine max (L.) Merrill) is one of the most widely used agricultural crops in the Brazilian economy, used to obtain oil and bran, which is an important source of protein. Soybeans contain more protein than any other commercially used plant speci